2013
DOI: 10.1177/2325967113513423
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Low-Field Magnetic Resonance Imaging Scanners for Evaluation of Knee Pathology Based on Arthroscopy

Abstract: Background:In recent years, few studies have evaluated low-field magnetic resonance imaging (MRI) diagnoses compared with intraoperative findings of the knee.Purpose:To determine the accuracy and sensitivity of low-field MRI scanners in diagnosing pathology of the menisci, cruciate ligaments, and osteochondral surfaces.Study Design:Cohort study (diagnosis); Level of evidence, 2.Methods:MRI examinations without intra-articular contrast were performed on 379 patients for knee pathologies over a 4-year period. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
13
0
4
Order By: Relevance
“…En el menisco lateral las cifras fueron de 51, 93, 84 y 73%. 7 Al compararse con el presente estudio, se tuvieron resultados más elevados en cuanto a porcentaje, pero coinciden con la dificultad para realizar el dictamen por imagen del menisco lateral.…”
Section: Wwwmedigraphicorgmxunclassified
“…En el menisco lateral las cifras fueron de 51, 93, 84 y 73%. 7 Al compararse con el presente estudio, se tuvieron resultados más elevados en cuanto a porcentaje, pero coinciden con la dificultad para realizar el dictamen por imagen del menisco lateral.…”
Section: Wwwmedigraphicorgmxunclassified
“…22 Low field MRI (< 0.5 T), although rarely used at present, is hypothesized to be highly suitable for musculoskeletal imaging. 23,24 Interestingly, Radzi et al 25 found that decreasing the main magnetic field (from 3 T to 1.5 T) resulted in a 16% reduction of metal artefacts. It is expected that low field MRI (0.25 T) would further decrease metal artefacts.…”
Section: Alternative Anchor Materialsmentioning
confidence: 99%
“…However, an increased main magnetic field is correlated with increased susceptibility artefacts in the presence of orthopaedic hardware (38,39). Traditional attempts to reduce metal artefacts primarily focus on the improvement of settings (e.g.…”
Section: 12 High-and Low-field Magnetic Resonance Imagingmentioning
confidence: 99%
“…However, reduction of the main magnetic field (low-field MRI < 0.5 T) might provide another option that would sufficiently diminish the susceptibility artefacts (38,39). Since high-field MRI provides better spatial and contrast resolution, low-field MRI is seldom used (51).…”
Section: 12 High-and Low-field Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation